Bowing to External Pressures: How the Threat of Lawsuits Dilutes Bias Response in Higher Education - Ryan A. Miller (AERA Open)
Bias response teams (BRTs) have proliferated in colleges and universities as administrative mechanisms to respond to hate and bias incidents on campuses. Advocacy groups have positioned BRTs within contemporary antidiversity culture wars and pressured institutions to abandon BRTs, alleging that they violate First Amendment protections. Through theoretical lenses anchored by repressive and creeping legalism, this multiple case study examined emerging alternatives to BRTs that are responsive to these external pressures. Administrator interviews and institutional documents reveal four emerging approaches: bias support resource, campus climate resource, free-speech resource, and informal/ad hoc resource. The designs of these alternatives demonstrate the outsize influence of external groups—particularly the threat of lawsuits from Speech First—and how institutions weakened and decentralized bias response functions to avoid external scrutiny. Implementation of these models prioritizes free-speech absolutism and can overshadow the initial need for creating bias response mechanisms on campus.